Publics of policing: expanding approaches to nodal policing - Cooper-Knock, S. J. (Policing and society, 2024)
The rise of private security across the globe has sparked concerns that a central public good is being corporatized, and that policing will no longer be guided by the interests of ‘the public'. In this article, we argue that state policing has never been in the interests of ‘the public'. Instead, like all policing actors, the state police create and serve something more finite: ‘a public'. By exploring the ‘publics of policing' we gain important insights into the constitutive role policing plays in producing socio-political communities. We suggest that this represents an important addition to the nodal governance framework, which currently overlooks the importance of what corporate, state and civic actors create when they engage in policing.